Magmatic–hydrothermal evolution of highly fractionated granites: Evidence from the Kuiqi miarolite in Fujian province, SE China. (1st June 2016) - Zeng, Lingjun; Bao, Zhiwei; Shan, Qiang; Yang, Wubin; Zhao, Yan; Li, Ningbo
Highlights: The melt inclusions show that the magmatic melt was volatile-rich. The ML-type and coexisting M- and V-type inclusions reflect the magmatic–hydrothermal evolution. The temperature and salinity of the fluid decrease toward the end of hydrothermal stage. Abstract: The Kuiqi miarolite, a highly evolved alkaline granite pluton, is situated in Fujian province, southeastern China. Quartz crystals from the Kuiqi miarolite contain abundant inclusions, which have preserved a complete record of the magmatic–hydrothermal evolution. Five inclusion type were identified, i.e., the melt (M-type), melt–fluid (ML-type), daughter mineral-bearing (S-type), vapor-rich (V-type), and aqueous (L-type) inclusions. Integrated petrographic, microthermometric and laser Raman spectroscopy studies demonstrate that the whole magmatic–hydrothermal evolution at Kuiqi comprises three stages, i.e., the magmatic, magmatic–hydrothermal and hydrothermal stages. The M-type inclusions (minimal trapping temperatures: ca. 710–800 °C) represent the melts entrapped at the magmatic stage of crystallization, while the occurrence of euhedral prismatic arfvedsonites in these melt inclusions indicates that the granitic magma was probably volatile-rich. At the magmatic–hydrothermal stage, both the ML-type inclusions ( Th  = ca. 500–710 °C) and coexisting M- and V-type inclusions reflect the presence of late magmatic fluid circulation and melt-volatile immiscibility, exhibiting a transition toward the hydrothermal stage. At the hydrothermal stage, the pressure and temperature (700–485 °C) drop may have led to oversaturation of the primary saline fluids, resulting in the phase separation a highly saline and a volatile-rich fluid occurred, accompanied by the widespread vapor–brine immiscibility. The L-type inclusions in the miarolitic quartz display bimodal salinity distribution: The Th and salinity of the inclusions at the bottom (L1 ) miarolitic quartz are ca. 303–427 °C and ca. 6.6–17.9 wt.% NaCl equiv, respectively, while that of the inclusions at the top (L2 ) are ca. 165–232 °C and ca. 0.2–5.7 wt.% NaCl equiv, respectively. This indicates a drop of fluid temperature and salinity during the miarolitic cavity formation. Moreover, the low homogenization temperatures and salinities of the L-type inclusions suggest an influx of meteoric water during the late hydrothermal evolution stage.